Comprehensive MRI simulation methodology using a dedicated MRI scanner in radiation oncology for external beam radiation treatment planning. Issue 1 (11th December 2014) - Paulson, Eric S.; Erickson, Beth; Schultz, Chris; Allen Li, X.
Abstract : Purpose: The use of magnetic resonance imaging (MRI) in radiation oncology is expanding rapidly, and more clinics are integrating MRI into their radiation therapy workflows. However, radiation therapy presents a new set of challenges and places additional constraints on MRI compared to diagnostic radiology that, if not properly addressed, can undermine the advantages MRI offers for radiation treatment planning (RTP). The authors introduce here strategies to manage several challenges of using MRI for virtual simulation in external beam RTP. Methods: A total of 810 clinical MRI simulation exams were performed using a dedicated MRI scanner for external beam RTP of brain, breast, cervix, head and neck, liver, pancreas, prostate, and sarcoma cancers. Patients were imaged in treatment position using MRI‐optimal immobilization devices. Radiofrequency (RF) coil configurations and scan protocols were optimized based on RTP constraints. Off‐resonance and gradient nonlinearity‐induced geometric distortions were minimized or corrected prior to using images for RTP. A multidisciplinary MRI simulation guide, along with window width and level presets, was created to standardize use of MR images during RTP. A quality assurance program was implemented to maintain accuracy and repeatability of MRI simulation exams. Results: The combination of a large bore scanner, high field strength, and circumferentially wrapped, flexible phased array RF receive coils permitted acquisition of thin slice images with high contrast‐to‐noise ratio (CNR) and image intensity uniformity, while simultaneously accommodating patient setup and immobilization devices. Postprocessing corrections and alternative acquisition methods were required to reduce or correct off‐resonance and gradient nonlinearity induced geometric distortions. Conclusions: The methodology described herein contains practical strategies the authors have implemented through lessons learned performing clinical MRI simulation exams. In their experience, these strategies provide robust, high fidelity, high contrast MR images suitable for external beam RTP.